Using Resource Consumption Accounting to determine Customer Cost of Banks - Abdullah Yaqoub, Fayahaa; Jamal Fadhil, Khaled (Journal of Economics and Administrative Sciences, 2020)
The Purpose of this Research show gap between a Normal Cost System and Resource consumption Accounting Applied in AL-Rafidin Bank. The Research explores that, how the idle capacity can be determined under resource consumption accounting, discuss the possibility of employing these energies. Research also viewed how costs can be separated into Committee and Attribute. Resource Consumption Accounting assists managers in pricing services or products based on what these services or products use from each Source. This Research has been proven that Resource consumption Accounting is more Normal Costing systems accurate In allocating indirect costs, especially in banks, because they are high. This Research provide an insight into the measurement of idle capacities quantitative and money within the Service sector generally, and Banks especially. The most important conclusions of this research that Resource consumption Accounting helps General Management of the Bank to exploit unused capacity to contribute to reducing the prices of products or services.